Performance analysis of enhanced 3D printed polymer molds for metal injection molding process - Altaf, K. (MDPI AG, 2018)
Conventionally, molds for metal injection molding (MIM) process are fabricated using metallic materials using conventional machining processes. Machined metal molds are resilient and therefore could be suitable for mass production of MIM parts. However, with the process of mass production leading to permanent hard tooling, the design is subjected to rigorous testing and iteration before finalization. During design analysis and the iteration process, the demand for MIM parts (part demand) is at low-volume. Therefore, machined metal molds could be costly and time consuming for low volume and customized end-use products. 3D printed molds could be a suitable choice for MIM production for such applications. The present study compares the performance of Fused Deposition Modelling (FDM) 3D printing (3DP) process made polymer molds with an aluminum mold for potential use in MIM process. It was observed that 3DP molds could successfully be used for a limited number of MIM cycles. Â© 2018 by the authors. Licensee MDPI, Basel, Switzerland.